Levels of Adiponectin and Soluble Tumor Necrosis Factor-α Receptor 2 (sNFαR2) in Obese Males with or without Fatty Liver - Agus Sulaeman; Syarifuddin Wahid; Ali Sulaiman; Gatot Susilo Lawrence (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Increased lipolysis in obese patients will cause elevated free-fatty acid level leading to insulin resistance. There are varied inflammatory cytokines (sTNFαR2) and anti-inflammatory cytokines (adiponectin) in obese patients, with and without fatty liver (FL). The aim of this study was to determine sTNFαR2 and adiponectin levels in obese patients with and without fatty liver. Method: This study was an observational study with cross-sectional approach, which was conducted between September 2008 and August 2009. The patients were 94 obese male with waist circumference ≥ 90 cm based on criteria of the International Diabetes Federation. Fatty liver was detected by ultrasonography; while adiponectin and sTNFαR2 levels in blood were analyzed by using ELISA Method and blood examination at the clinical laboratory. Results: Levels of adiponectin and sTNFαR2 were different between obese patients with and without FL. The adiponectin level was 3.10 ± 1.14 in patients with FL and was 3.52 ± 1.07 in patients without FL; while the sTNFαR2 were 23.92 ± 6.00 (FL) and 20.61 ± 5.29 (without FL). In patients with low adiponectin level ( 3.33 µ g/L) and high sTNFαR2 level ( 21.78 pg/dL), there was relatively higher occurrence of fatty liver compared to the other patients. Conclusion: Obese patients with fatty liver have higher sTNFαR2 level than patients without fatty liver. Moreover, obese patients with fatty liver have lower adiponectin level compared to patients without fatty liver. Patients with low adiponectin level and high sTNFαR2 level have higher incidence of fatty liver than subjects with high adiponectin level and low sTNFαR2 level. Keywords: adiponectin, soluble tumor necrosis factor α receptor 2 (sTNFαR2), obese, fatty liver